Characteristics of early repolarization parameters and prognostic implications in the general ambulatory Korean population. (15th January 2017) - Cho, Min Soo; Kwon, Chang Hee; Nam, Gi-Byoung; Lee, Woo Seok; Hwang, Ki Won; Kim, Yong Giun; Choi, Hyung Oh; Kim, Sung-Hwan; Kim, Jeongsoon; Nam, Hyo-Jung; Min, Sun-Yang; Kim, Minsu; et al.
Abstract: Background: We tested a hypothesis that the 2 fundamental components of early repolarization (ER), J wave and ST elevation (STE) might have different prevalence and prognostic implications. Methods: The study population comprised 26, 345 general ambulatory Korean subjects (mean 48.0 ± 10.2 years old, 53.2% male) who underwent medical checkups from January 2002 to December 2002. ER was found in 2950 subjects (11.2%), who were divided into 3 groups (J [J wave only, n = 1874, 7.1%], JST [both J wave and STE, n = 489, 1.8%], and ST [STE only, n = 587, 2.3%]). Results: The prevalence of STE decreased with age, whereas J waves remained at a constant level in all age groups. The most common pattern of ER was the J pattern, with a horizontal/descending ST segment in the inferior leads; in lateral precordial leads, ST or JST patterns with ascending ST segments were more common. During the mean follow-up of 126.0 ± 11.1 months, a total of 710 subjects died (2.7%). Subjects in the J group were at higher risk (Hazard ratio 1.60, 95% confidence interval 1.27–2.01, p < 0.001), while those in the JST and ST groups showed similar survival outcomes compared to controls without J waves or STE. Conclusions: J waves and STE showed different age and lead distributions and prognostic implications. The presence of the J wave itself was associated with a higher relative risk of mortality. However, due to the low event rate, its clinical significance appears to be limited.